Teknologi Sederhana Pemanfaatan Ampas Kopi untuk Pupuk Organik Cair - Sri Wulandari; Twenty Mariza Syafitri; Elia Fahmi Sella; Bayu Cahya Ningrat; Nurjanah Setia Wangi (Jurnal Dehasen Untuk Negeri, 2023)
Fertilization is one of the supporting factors increasing the quality and productivity of agricultural land. Coffee grounds have the potential to be used as organic fertilizer due to the content of various environmentally friendly substances, but some people, especially Kayu Manis Village, consider coffee grounds to be waste that cannot be used anymore. Community service activities have been carried out aim to increase the knowledge, awareness, and skills of farmer groups in Kayu Manis Village, Rejang Lebong Regency in utilizing coffee grounds for liquid organic fertilizer using simple technology. The activity was carried out in two stages, socialization of the potential, benefits, and content of coffee grounds for liquid organic fertilizer, demonstration of simple technologies for making liquid organic fertilizer from coffee grounds. The results showed the enthusiasm participant was very high, as indicated by the level of attendance, enthusiastic participants asking questions, and responsiveness. This activity made the Cinnamon Village farmer groups have better knowledge and skills regarding the potential of coffee grounds for liquid organic fertilizer. The simple technology used to make liquid organic fertilizer from coffee grounds makes it easy for farmer groups to apply it, besides that it is supported by low costs.